Keterkaitan Pengaruh Iklim Terhadap Angka Kejadian Tuberkulosis Berbasis Web Gis - Manaf, Abdul; Hermawan, Erwin; Kamilah, Nurul (Rifa'Institute, 2023)
Management of pulmonary tuberculosis (TB) in Bogor City is still a priority in health care. The high number of TB cases in the Lawang Gintung Health Center area in the 2017-2019 period reached 126 new cases. Where the most new cases were in the Muarasari Village with a total of 52 new cases of TB. This research method uses the spatial interpolation method to determine the distribution of climate and its association with the incidence of new cases of pulmonary TB. Through the development of spatial interpolation GIS, it is known that the pattern of distribution of cases per month in the area of ??the Public Health Center in terms of the relationship between climate and the development of new cases of TB in the area of ??the Lawang Gintung public Health center. Incidence Rate in the region public Health center Lawang Gintung per month during 2017-2019 was highest in February with an IR value of 8.7 per 10,000 people/population. The increase in the IR value in each month is accompanied by an increase in the average value of rainfall (mm²), air temperature (°C), and humidity (%). Where in January the IR value was 2.2, increasing in February to 8.7 with an average rainfall value per month of January 15.4 mm² and in February it increased to 25.3 mm². Followed by increasing the value of air temperature and humidity. Correlation of climate to the incidence of new cases of pulmonary TB in the region public Health center Lawang Gintung is known that rainfall is positive with an R² value of 0.50. Air temperature is negative where R² is 0.01 and humidity is positive with R² value is 0.17.